Creating Animated Short Stories with Digital Apps: Project-Based Learning in EFL Classroom - Santiana, Santiana; Silvani, Dea; Syakira, Sitti; Miguel Cardoso, Luis; Temitope Sulaimon, Jamiu; Khan, Tariq (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This study aims to investigate the benefits of implementing project-based learning (PBL) to create short stories using digital apps at the university level. Thirty-nine students from the English Education Department at a university in West Java were purposively selected as participants because they were enrolled in a Digital Storytelling course, making them directly relevant to the study’s objectives. They used a digital application to facilitate a project that required them to visualize their narratives as animated videos. This study employed a qualitative case study approach, with data collected through student reflections, observations, and semi-structured interviews. The data were analyzed thematically, following coding, categorization, and interpretation processes to identify recurring themes and patterns in students’ experiences. The findings indicate that students improved their listening, speaking, reading, and writing skills while enhancing their communication, teamwork, problem-solving, and technical abilities. Moreover, PBL fostered creativity, critical thinking, and collaborative engagement, creating a positive and supportive learning environment. These results suggest that integrating PBL with digital storytelling can significantly strengthen language proficiency and 21st-century skills, highlighting the need for institutional support to overcome technical challenges.